THE UTILIZATION OF SOLAR CELLS AND WATER TURBINES AS SOURCING VOLTAGE ON POWER MULTI-BASED HYDROPONIC - Fifiana Putri Suwenda; Zainal Abidin; Ulul Ilmi (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2021)
The use of electric power is significant to supply water pumps which are usually obtained from PLN electricity. The utilization of electricity from new renewable energy such as solar panel electricity and water turbines has not been used too much to cultivate hydroponic plants. Therefore, combining electric power (hybrid) between solar cells and water turbines is needed to supply electricity on hydroponic technology in conserving electrical energy for the future. Based on these problems, this study conducted various tests to create a design that could be used for energy use in hydroponic plants. The method used includes electrical and systematic design. The steps taken include the stage of literature study, designing, manufacturing hardware, integrating the system, and testing and analyzing the system. These theories can discover solar panels, solar chargers, battery endurance, thief joule circuits, and water turbines. This study uses several tests, including solar panels, solar chargers, battery endurance, thief joule series, and water turbines. Solar panels function to capture sunlight, solar chargers to store electrical voltage to batteries, battery endurance functions to find out how many batteries can store electricity, a series of thief joules to increase voltage, and water turbines to produce voltage. From all data tests, solar panels and water turbines are a source of voltage that the battery will store via a solar charger, and then from the battery, it will be supplied to the hydroponic circuit as a source of voltage.